Theory in Perpetual Motion and Translation: Assemblage and Intersectionality in Feminist Studies - Bogic, Anna (Atlantis, 2017)
The article examines the French theoretical concept of agencement developed by Gilles Deleuze and Félix Guattari and its English translation as assemblage which has been widely used in feminist, philosophical, and theoretical work. Starting with Jasbir Puar’s critique of intersectionality, I argue that although assemblage may now be called upon to provide a corrective to intersectionality, not too long ago, intersectionality, with very similar arguments, was viewed as the most promising alternative to categorical thinking.